The right to environment at sea: a human rights-based approach to marine environmental protection - Wang, Guanding; Yu, Liang; Chen, Xi (Frontiers in Marine Science, 2025)
The marine environment is becoming increasingly fragile and complex, posing serious threats to fundamental human rights. Despite the growing interconnection between marine protection and human rights, a significant gap persists between the international law of the sea and human rights law. The former remains state-centered and largely overlooks human rights, while the latter has developed primarily in land-based contexts and offers limited tools for protecting the marine environment. This article advances a human rights–based approach by introducing the concept of “the right to environment at sea” and illustrating its normative content. It identifies the right-holders, duty-bearers, and corresponding obligations, and demonstrates the unique advantages of this framework in addressing deep-sea mining, marine pollution, and biodiversity protection. It further explores potential pathways to activate the proposed right, including systemic treaty interpretation under Article 31(3)(c) of the Vienna Convention and procedural mechanisms through human rights treaty bodies, the Human Rights Council, regional human rights courts, the International Tribunal for the Law of the Sea, and the International Court of Justice. It argues that this rights paradigm adds values to marine environmental governance by strengthening State obligations and accountability.